Survey geometry and the internal consistency of recent cosmic shear measurements. Issue 4 (15th June 2018) - Troxel, M A; Krause, E; Chang, C; Eifler, T F; Friedrich, O; Gruen, D; MacCrann, N; Chen, A; Davis, C; DeRose, J; Dodelson, S; Gatti, M; et al.
ABSTRACT: We explore the impact of an update to the typical approximation for the shape noise term in the analytic covariance matrix for cosmic shear experiments that assumes the absence of survey boundary and mask effects. We present an exact expression for the number of galaxy pairs in this term based on the survey mask, which leads to more than a factor of three increase in the shape noise on the largest measured scales for the Kilo-Degree Survey (KiDS-450) real-space cosmic shear data. We compare the result of this analytic expression to several alternative methods for measuring the shape noise from the data and find excellent agreement. This update to the covariance resolves any internal model tension evidenced by the previously large cosmological best-fitting χ 2 for the KiDS-450 cosmic shear data. The best-fitting χ 2 is reduced from 161 to 121 for 118 degrees of freedom. We also apply a correction to how the multiplicative shear calibration uncertainty is included in the covariance. This change shifts the inferred amplitude of the correlation function to higher values. We find that this improves agreement of the KiDS-450 cosmic shear results with Dark Energy Survey Year 1 and Planck results.